2019
DOI: 10.1039/c9sc02067e
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic protodeboronation of pinacol boronic esters: formal anti-Markovnikov hydromethylation of alkenes

Abstract: Methane is formally added to alkenes via sequential hydroboration, Matteson-CH2-homologation and radical protodeboronation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 63 publications
(50 reference statements)
0
24
0
Order By: Relevance
“…If α‐perfluoroalkylated ketones are formed as initial products after C−B to C=O functional group transformation, HF elimination was observed during purification leading to α,β‐unsaturated ketones. The high synthetic potential of the stereospecific radical‐induced 1,2‐boron ate rearrangement was further demonstrated by its application to novel formal total syntheses of δ‐( R )‐coniceine and indolizidine 209B, starting with the enantiopure Boc‐protected pyrrolidine boronic ester (Scheme b) . Via a radical polar crossover reaction using α‐iodoacetates as C‐radical precursors, two C−C‐bonds are formed in the key reaction.…”
Section: Radical‐induced 12‐boron Ate Shifts To Sp2 Carbonsmentioning
confidence: 99%
“…If α‐perfluoroalkylated ketones are formed as initial products after C−B to C=O functional group transformation, HF elimination was observed during purification leading to α,β‐unsaturated ketones. The high synthetic potential of the stereospecific radical‐induced 1,2‐boron ate rearrangement was further demonstrated by its application to novel formal total syntheses of δ‐( R )‐coniceine and indolizidine 209B, starting with the enantiopure Boc‐protected pyrrolidine boronic ester (Scheme b) . Via a radical polar crossover reaction using α‐iodoacetates as C‐radical precursors, two C−C‐bonds are formed in the key reaction.…”
Section: Radical‐induced 12‐boron Ate Shifts To Sp2 Carbonsmentioning
confidence: 99%
“…Our group has been focusing on the development of new methods for the synthesis and application of alkyl-Bpin. [45][46][47][48][49][50][51][52] Considering the challenge of the less reactive Aggarwal group 41,42 Ley and co-workers [38][39][40] Studer group 43 Scheme 1 | (a and b) Photoinduced generation of alkyl radicals from alkyl-Bpin and its application in a transitionmetal-free alkynylation. LG = -SO 2 Ph.…”
Section: Resultsmentioning
confidence: 99%
“…The generated alkyl radicals reacted with olefins to form Csp 3 -Csp 3 bonds. The Studer group 43 also used this activation strategy to achieve protodeboronation of alkyl-Bpin. However, the preformation of ate complex using PhLi at low-temperature and solvent-switch operation make this strategy less practical.…”
Section: Introductionmentioning
confidence: 99%
“…Although the base-promoted protodeboronation 9 has been known as a side reaction in Suzuki-Miyaura coupling reactions, a few recent reports have revealed that the protodeboronation of organoboron compounds promoted by acid 10 or complexes containing metals, such as gold, 11 silver, 12 copper, 13 and bismuth, 14 can be applied in synthetic organic transformations. 15 Aggarwal 16,17 reported the protodeboronation of tertiary boronic esters with essentially complete retention of configuration, promoted by a stoichiometric amount of CsF,H 2 O-or TBAF•3H 2 O (Scheme 2). They suggest that the protodeboronation of boronic esters proceeds via protonation of a tetracoordinated borate intermediate generated by coordination of a fluoride anion to the boron atom of the boronic esters.…”
Section: Letter Syn Lettmentioning
confidence: 99%